Investigation on fatigue performance of cold expansion holes of 6061-T6 aluminum alloy - Wang, Yan-li; Zhu, You-li; Hou, Shuai; Sun, Han-xiao; Zhou, Yong (International journal of fatigue, 2017)
•Cold expansion got a 247% reward comparing to the plain specimens.•Fatigue crack bypassing characteristic was discovered in cold expanded specimens.•Shear mode secondary crack was formed in cold expanded specimens.•Residual compressive stress slowed down the fatigue crack growth rate effectively.•Grain boundary and the angle of favored slipping planes affected crack growth path. The effect of direct cold expansion on the fatigue behavior of fasten holes of AA6016-T6 was investigated. Results revealed that: (1) The fatigue life of the cold expanded (CE) specimens increased by 2.47 times compared to that of the non-cold expanded (NCE) specimens, and all the fatigue origins of the CE specimens initiated at the hole’s corner of the mandrel inlet side; (2) It was interesting to find that the fatigue crack has bypassed the tri-directional compressive stress domain in all the fracture surfaces of the CE specimens, which was believed to be beneficial to the fatigue life prolongation; (3) A ‘shear mode secondary crack’ different from ‘ordinary secondary crack’ was formed in the fracture surfaces of the CE specimens, which was generated by the residual shear stress imparted by the CE process; (4) Residual compressive stress could effectively slow down the fatigue crack growth rate; (5) Grain boundary and the angle of favored slipping planes of neighbor grains affected the fatigue crack propagation path evidently.